Associations of Leukocyte Telomere Length With Trait Resilience, Adverse Childhood Experiences, and Psychological Distress Among Expecting Parents in the FinnBrain Birth Cohort - Mondolin, Viivi; Karlsson, Hasse; Perasto, Laura; Paunio, Tiina; Vitikainen, Emma; Martens, Dries S.; Karlsson, Linnea; Tuulari, Jetro J.; Kataja, Eeva-Leena (Elsevier BV, 2025)
Background: Telomere attrition has previously been associated with mental health problems and adverse childhood experiences (ACEs). Resilience has been shown to protect against mental health problems even in the context of ACEs. In this study, we examined the associations between leukocyte telomere length (LTL), symptoms of psychological distress, ACEs, and trait resilience. We examined whether LTL mediates the negative effects of ACEs and whether trait resilience moderates the association between LTL and distress.
Methods: The study population was drawn from the ongoing FinnBrain Birth Cohort Study and included 342 mothers and 339 fathers who had provided blood samples and questionnaire data during pregnancy. Questionnaire data included the Connor-Davidson Resilience Scale 10, Edinburgh Postnatal Depression Scale, Symptom Checklist-90, and Trauma and Distress Scale. Data analysis included regression analysis, mixed-methods models, and statistical evaluation.
Results: ACEs were associated with depressive and anxiety symptoms. However, contrary to the initial hypothesis, LTL was not associated with ACEs or distress symptoms and thus did not mediate their association. Furthermore, resilience was not associated with LTL and did not moderate the possible association between LTL and distress symptoms.
Conclusions: We found no association between TL and ACEs, psychological distress, or trait resilience. The mild distress symptoms, limited exposure to high ACEs, and the predominantly moderate to high socioeconomic status in the sample may be relevant to interpreting these findings. Encouragingly, not all ACEs necessarily lead to telomere attrition.